Searching and Visualization of References in Research Documents - Firnas Nadirman; Ahmad Ridha; Annisa Annisa (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2014)
This research aims to develop a module for information retrieval that can trace references from bibliography entries of research documents, specifically those based on Bogor Agricultural University (IPB)’s writing guidelines. A total of 242 research documents in PDF from the Department of Computer Science IPB were used to generate parsing patterns to extract the bibliography entries. With modified ParaTools, automatic extraction of bibliography entries was performed on text files generated from the PDF files. The entries are stored in a database that is used to visualize author relationship as graphs. This module is supplemented by an information retrieval system based on Sphinx search system and also provides information of authors’ publications and citations. Evaluation showed that (1) bibliography entry extraction missed only 5.37% bibliography entries caused by incorrect bibliography formatting, (2) 91.54% bibliography entry attributes could be identified correctly, and (3) 90.31% entries were successfully connected to other documents.